Failed Expectations: The Protestant Reformation and the Orthodox Church - Roddy, Nicolae (Journal of religion & society. Supplement, 2019)
During the latter half of the sixteenth century, a handful of Tübingen theologians initiated informal correspondence with the ecumenical patriarch of the Orthodox Church, Jeremias II of Constantinople, in which they expressed the hope and expectation that he would acknowledge the orthodoxy of Lutheran faith and practice. Jeremias’s response was gracious, but uncompromising in its assertion that the only way a Christian could be considered truly orthodox would be to receive chrismation and enter into the sacramental life of the Orthodox Church. The Lutheran theologians stepped up their defense on the basis of their vast knowledge and understanding of scripture and patristics, only to be met by more of the same from Constantinople. Tensions increased with each exchange as conciliatory overtures melted away to reveal each side’s defining, non-negotiable core position. Upon delivering a delayed third response, the Patriarch invited the Lutherans to remain in contact, but admonished them never again to raise doctrinal matters with the Orthodox Church. This paper provides the historical backdrop for the main issues that continue to plague Lutheran-Orthodox dialogue to the present day.